1996
DOI: 10.1093/oxfordjournals.humrep.a019244
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine insemination: evaluation of the results according to the woman's age, sperm quality, total sperm count per insemination and life table analysis

Abstract: We report on 332 infertile couples who underwent 1115 cycles of intrauterine insemination (IUI) with washed husband's semen. The indication for IUI was an abnormal post-coital test due to either a male or cervical infertility factor. The mean number of IUI cycles per patient was 3.4, the overall pregnancy rate 18.7%, and the pregnancy rate per cycle 5.6%. The cumulative pregnancy rate calculated by life table analysis showed that 16.0% of pregnancies occurred in the first three treatment cycles, while the cumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
96
1
7

Year Published

1999
1999
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(112 citation statements)
references
References 19 publications
8
96
1
7
Order By: Relevance
“…But, when NSMI exceeded 10 million, our results showed a slight non-significant decrease in pregnancy rate, which could be related to excessive production of free radicals by the spermatozoa. Most authors recommend IVF when the number of motile sperm is <1 × 10 6 [11, 12, 16 and 17]Some authors suggested using the total number of motile spermatozoa of the initial sperm count (before semen treatment) as the criterion for choosing between IUI and IVF, and have recommended threshold values ranging from 5 to 10 × 10 6 [18,19]. In other studies, total sperm motility before semen treatment was mentionedwith a cut-off level between 30 and 50% [20, 21, 22 and 23].The usefulness of this criterion, however, is limited by the variability of quality from one ejaculation to another, as well as the variable results of sperm preparations.Our study shows no significant difference in sperm motility before sperm treatment, between patients who achieved pregnancy and those who failed Sperm morphology using strict criteria is well known as one of the best predictors of IVF outcome [24, 25 and 26].…”
Section: Discussionmentioning
confidence: 99%
“…But, when NSMI exceeded 10 million, our results showed a slight non-significant decrease in pregnancy rate, which could be related to excessive production of free radicals by the spermatozoa. Most authors recommend IVF when the number of motile sperm is <1 × 10 6 [11, 12, 16 and 17]Some authors suggested using the total number of motile spermatozoa of the initial sperm count (before semen treatment) as the criterion for choosing between IUI and IVF, and have recommended threshold values ranging from 5 to 10 × 10 6 [18,19]. In other studies, total sperm motility before semen treatment was mentionedwith a cut-off level between 30 and 50% [20, 21, 22 and 23].The usefulness of this criterion, however, is limited by the variability of quality from one ejaculation to another, as well as the variable results of sperm preparations.Our study shows no significant difference in sperm motility before sperm treatment, between patients who achieved pregnancy and those who failed Sperm morphology using strict criteria is well known as one of the best predictors of IVF outcome [24, 25 and 26].…”
Section: Discussionmentioning
confidence: 99%
“…Others have reported that the cumulative pregnancy rate plateaus by the ninth IUI cycle (16). As in most forms of infertility treatment, the success of IUI is largely influenced by the etiology of the infertility and the sperm quality.…”
Section: Discussionmentioning
confidence: 99%
“…The per cycle pregnancy rate is influenced by various factors and is typically in the range of 5-20%. Cumulative pregnancy rate after 3-4 treatments is in the range of 25-40% [1,[3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%